ANALISIS RANTAI PASOK CABAI MERAH DI KOTA JAMBI PROVINSI JAMBI - Ningsih, Iin Widya; Wahyuni, Ira; Malik, Adlaida (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
This study was aimed at: (1) Knowing the description of the supply chain of red chili and, (2) Analyzing the supply chain performance of red chili in the city of Jambi. This research was conducted in Jambi City starting from the Angso Duo Central Market using primary data and secondary data. The analytical method used is descriptive using the Food Supply Chain Network (FSCN) framework and the marketing efficiency approach, through marketing margin analysis, farmer's share analysis and profit-to-cost ratio. The number of respondents was 30 farmers, 17 wholesalers and 8 wholesalers. From the research results it can be seen that (1): the supply chain of red chili still does not meet the desired criteria in the FSCN analysis framework, but it already has a clear target market but supply chain management is not well managed, red chili comes from two sources, namely from farmers and from various production centers through wholesalers, (2) the performance of the supply chain of red chili in Jambi City shows inefficient conditions. This can be seen from the results of the analysis of marketing margins, farmer's share, and profit-to-cost ratios which show that they have not been equally profitable for each member of the supply chain involved. The marketing channel for red chili from farmers that shows the most efficient condition is the marketing channel I. Meanwhile, the supply channel for red chili from various production centers through wholesalers shows the most efficient condition is supply channel II.